Higher Levels of High-Sensitivity C-Reactive Protein Is Positively Associated with the Incidence of Hyperuricemia in Chinese Population: A Report from the China Health and Retirement Longitudinal Study. (20th May 2020) - Dai, Hui-Xu; Zhao, Zhi-Ying; Xia, Yang; Wu, Qi-Jun; Zhao, Yu-Hong
Abstract : Purpose . The aim of the present cohort study was to explore the longitudinal association between high-sensitivity C-reactive protein (CRP) and hyperuricemia in Chinese population. Furthermore, we conducted subgroup analyses to explore this association according to age, sex, and body mass index. Methods . A total of 5, 419 healthy participants were enrolled in the final cohort analysis. The high-sensitivity CRP level was measured by immunoturbidimetric assay. Hyperuricemia was defined as serum uric acid ≥7.0 mg/dL (416  μ mol/L) in men and ≥6.0 mg/dL (357  μ mol/L) in women. Multivariate logistic regression was used to analyze the association. Results . During the 4 years follow-up, 474 participants developed hyperuricemia. Compared with participants in the lowest tertile of high-sensitivity CRP, the multivariate-adjusted odds ratio (OR) (95% confidence interval [CI]) for incident hyperuricemia in the highest tertile was 1.36 (1.02, 1.82). In the subgroup analyses, high-sensitivity CRP was positively associated with the incidence of hyperuricemia after multivariate adjustments (P   for   trend = 0.04 ) in women. Compared with the women in the lowest tertile of high-sensitivity CRP, the multivariate-adjusted OR (95% CI) in the highest tertile was 1.69 (1.10, 2.66). No statistically significant association was found in other subgroups. Conclusions . The findings of this prospective cohort study suggest that higher level of high-sensitivity CRP is an independent risk factor for hyperuricemia in Chinese, especially in women.